Matrix Isolation Infrared Spectra and Photochemistry of Hydantoin - Nunes, Claudio M.; Fausto, Rui; ILDIZ, GÜLCE ÖĞRÜÇ (Amer Inst Physics, 2 Huntington Quadrangle, Ste 1No1, Melville, Ny 11747-4501 USA, 2013)
Hydantoin (C3H4N2O2, 2,4-imidazolidinedione) was isolated in argon matrix at 10 K and its infrared spectrum and unimolecular photochemistry were investigated. The molecular structure of the compound was studied both at the DFT(B3LYP) and MP2 levels of approximation with valence triple- and quadruple-zeta basis sets (6-311++G(d,p); cc-pVQZ). It was concluded that the minima in the potential energy surfaces of the molecule correspond to C-1 symmetry structures. However, the energy barrier separating the two-equivalent-by-symmetry minima stays below their zero-point energy, which makes the C-s symmetry structure, which separates the two minima, the experimentally relevant one. The electronic structure of the molecule was studied in detail by performing the Natural Bond Orbital analysis of its electronic configuration within the DFT(B3LYP)/cc-pVQZ space. The infrared spectrum of the matrix isolated compound was fully assigned also with help of the theoretically predicted spectrum. Upon irradiation at lambda = 230 nm, matrix-isolated hydantoin was found to photofragment into isocyanic acid, CO, and methylenimine.
Keywords: Cambridge Structural Database; Crystal-Structures; Vibrational-Spectra; Mp2 energy; Ab Initio; x-ray; Hydrogen; Spectroscopy; Derivatives; Density; Cambridge Yapısal Veri Tabanı; Kristal Yapıları; Titreşim-Spektrumları; Mp2 Enerjisi; Ab Initio; Röntgen; Hidrojen; Spektroskopi; Türevler; Yoğunluk